Effect of PVC on ionic conductivity, crystallographic structural, morphological and thermal characterizations in PMMA-PVC blend-based polymer electrolytes - Ramesh, S.; Liew, Chiam-Wen.; Morris, E.; Durairaj, R. (Elsevier Science Bv, 2010)
In this paper temperature dependence of ionic conductivity crystallographic structural morphological and thermal characteristics of polymer blends of PMMA and PVC with lithium bis(trifluoromethanesulfonyl) imide (LiTFSI!) as a dopant salt are investigated The study on the temperature dependence of ionic conductivity shows that these polymer blends exhibit Arrhenius behavior The highest ionic conductivity was achieved when 70 wt% of PMMA was blended with 30 wt% of PVC Xray diffraction (XRD) and scanning electron microscopy (SEM) reveal the amorphous nature and surface morphology of polymer electrolytes respectively In DSC analysis it was found that the glass transition temperature (TO and melting temperature (T(m)) decreased whereas the decomposition temperature (T(d)) increased In contrast the shift towards higher decomposition temperature and decrease in weight loss of polymer electrolytes in TGA studies indicates that the thermal stability of polymer electrolytes improved (C) 2010 Elsevier B V All rights reserved